Selection of parameters for the study and assessment of the transport and operational condition of the road - Burtyl, Yuri V.; Kapski, Denis V.; Filippova, Nadezhda A.; Neretin, Alexander A. (International journal of advanced studies, 2025)
Background.The main objective of the study was to create a model that allows more accurate assessment of the performance characteristics of roads using data collected over more than 20 years. The rationale for this study is the need to improve methods for assessing the condition of road surfaces, especially in the context of increasing requirements for the safety and quality of transport infrastructure. Assessing the condition of roads is an important task for standardizing and planning their repair and maintenance, which in turn affects road safety and budget savings. Purpose. Practical improvement of methods of working with road infrastructure, increasing its reliability and safety, which is extremely important for all road users. Materials and methods. Based on theoretical and experimental studies, a linear model for calculating the reliability of road surfaces has been developed. This proposed linear model has also received experimental confirmation, as a result of which the calculated correlation coefficients for the distribution law have been established. Results. Based on theoretical and experimental studies, a linear model for calculating the reliability of road surfaces has been developed. This proposed linear model has also received experimental confirmation, as a result of which the calculated correlation coefficients for the distribution law have been established.